2019
DOI: 10.1186/s40693-019-0084-2
|View full text |Cite|
|
Sign up to set email alerts
|

Community signals of the effect of Didymosphenia geminata (Lyngbye) M. Schmidt on benthic diatom communities in Chilean rivers

Abstract: Background: Didymosphenia geminata (Lyngbye) M. Schmidt is a freshwater invasive benthic diatom native to oligotrophic systems of the Northern Hemisphere. Since 2010, freshwater systems of south-austral Chile, have experienced a progressive invasion of this species between 37°18′ S and 54°30′ S. This invaded area is characterized by biogeographic heterogeneity, anthropic pressure and lack of knowledge. The objective of this study was to analyze the effect of D. geminata on the community structure of benthic di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 60 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…The authors did not observe species exclusion; however, it was observed that D. geminata is inclined towards a particular group of diatom species. This inclination can displace other diatom species and, therefore, cause different types of impacts, such as alterations in fluvial trophic webs [11].…”
Section: How Harmful Is This Species To the Canadian Environment And Public Health?mentioning
confidence: 99%
“…The authors did not observe species exclusion; however, it was observed that D. geminata is inclined towards a particular group of diatom species. This inclination can displace other diatom species and, therefore, cause different types of impacts, such as alterations in fluvial trophic webs [11].…”
Section: How Harmful Is This Species To the Canadian Environment And Public Health?mentioning
confidence: 99%
“…Reanalysis of the Puelo and Petrohue rivers in southern Chile confirmed the presence of mucilage‐producing forms of Didymosphenia from Peulo river and the presence of the genus in the Petrohue River, but without the production of mucilage masses likely due to the higher P levels of the latter system (Bravo et al, 2019). Diatoms assemblages from samples collected in rivers from south‐austral Chile from 2010 to 2017 contained higher numbers of small, pedunculate diatoms, and became more homogenized between basins in the presence of Didymosphenia , in contrast with the more variable assemblage structures of rivers without Didymosphenia (Salvo Pereira & Oyanedel Pérez, 2019).…”
Section: Algaementioning
confidence: 99%